ACADEMIC INFORMATION SYSTEM USER SATISFACTION MODEL USING TECHNOLOGY ACCEPTANCE MODEL (TAM) WITH END USER COMPUTING SATISFACTION (EUCS) MODIFICATION - NUROHMAN; NURHAYATI (CV KULTURA DIGITAL MEDIA, 2021)
User satisfaction with system performance is a benchmark for applying information technology. Academic Information System faculty of Compur Science University of Duta Bangsa Surakarta are used as a media support the campus academic process.This study aims to determine the relationship between content (content), the level of accuracy of the system (accuracy), format, easy of use, timeliness, organizational support, user attitudes towards the information system and perceived attitude of top management on the level of satisfaction of using the academic information system in faculty of Computer Science, University of Duta Bangsa Surakarta. This research is a descriptive study used technology acceptannce model (TAM) with modified End User Computing Satisfaction (EUCS) approach method. The result of this study was to determine the relationship between content (content), the level of accuracy of the system (accuracy), format, ease (easy of use), timeliness, organizational support, user attitudes towards the information system and perceived attitude of top management on the level of satisfaction of using the academic information system in faculty of Computer Science, University of Duta Bangsa Surakarta.